MYOCARDIAL INFARCTION TYPE 4TH: FEATURES OF THE COURSE, PREVENTION AND MANAGEMENT OF PATIENTS AFTER PERCUTANEOUS CORONARY INTERVENTIONS - N. G. Pravdyuk; A. V. Novikova; E. A. Korolyеv (Klinicist)
To date, cardiovascular diseases occupy the first place in the structure of total morbidity and mortality in many countries. In 2013 in the Russian Federation from cardiovascular disease died 1 million 799 thousand people, from the bottom 529.8 thousand from coronary heart disease, the primary role belongs to myocardial infarction and its complications. Currently, the "gold standard" for the diagnosis of coronary heart disease, including myocardial infarction, remains coronary angiography; the main objectives of coronary angiography are to assess the features of the coronary anatomy, determination of the possibility of endovascular treatment of myocardial infarction and revascularization by stent implantation. Despite the constant improvement of technology and the progress made in relation to pharmacological support, percutaneous coronary intervention (PCI) is an invasive manipulation, which is associated with a certain risk. Diagnostic criteria for myocardial infarction 4a type include increasing the level of troponin above 5 rules of 99th the upper threshold reference values within 48 hours after the PCI procedure, in patients with normal troponin increased (≤ 99th the upper threshold reference values), or a level of troponin 20 % or more in patients with initial high level troponin combined with evidence of prolonged myocardial ischemia. Stent when performing percutaneous coronary interventions, accompanied by the activation of thrombogenic reactions, can lead to thrombosis and development 4b type. To the diagnostic signs of the myocardial infarction 4b type are the stent thrombosis, angiographic proven and/or at autopsy, in combination with increased troponin level at least one greater than the 99th the upper threshold reference values. Stent when performing PCI, accompanied by the activation of thrombogenic reactions, can lead to thrombosis and development myocardial infarction 4b type. The diagnostic signs myocardial infarction 4b type are the stent thrombosis, angiographic proven and/or at autopsy, in combination with increased troponin level at least one greater than the 99th the upper threshold reference values. You should consider the fact that the setting of drug-eluting stents increases the period of their endothelization after implantation, which in turn increases the likelihood of late thrombosis and is an indication for long-term dual antiplatelet therapy. The article describes the varieties of myocardial infarction associated with PCI, an algorithm for the diagnosis and management of patients in accordance with current clinical recommendations.